THE CONCEPT OF ENVIRONMENTAL JUSTICE IN THE BRAZILIAN DISSERTATIONS AND THESIS IN ENVIRONMENTAL EDUCATION. A PANORAMIC AND PRODUCTION CONTEXTS STUDY - Angeli, Thais [UNESP]; Carvalho, Luiz Marcelo de [UNESP] (Univ Metodista Piracicaba-unimep, 2019)
In this article, we try to systematize some data about the context of production of Brazilian dissertations and theses on environmental education which problematize issues related to environmental justice, as well as to analyze the educational contexts and privileged study themes in these works. This is a qualitative, documentary and state-of-the-art research, which is part of the Environmental Education Project in Brazil: analysis of academic production - theses and dissertations (EArte Project). In this sense, it was possible to observe that the first work on EA that problematized the concept of environmental justice was published in 2004 and that, in this academic production that establishes relations between environmental education and environmental justice, the Southeast, South and Midwest regions and the postgraduate programs of the Education area of UFMT, UFRJ and Furg can be highlighted. It was also observed that the analyzed research involves the school and non-school context, with the central objective being the search for a formation focused on social transformation and environmental justice.
Keywords: ENVIRONMENTAL EDUCATION; ENVIRONMENTAL JUSTICE; RESEARCH